Identifikasi Jamur Aspergillus sp. pada Ikan Asin Yang Dijual di Pasar Sentral Kabupaten Pinrang - Salnus, Subakir; Islawati; Jumrah, Elfira (Jurnal TLM Blood Smear, 2024)
Indonesia is a tropical area. Erratic climate change causes many diseases, especially infectious diseases caused by fungi. One of the fungi that commonly contaminates food is Aspergillus sp. This type of fungus produces various types of toxins which can cause quite serious illnesses in humans. Acute diseases caused by the Asprgillus sp. fungus can attack the central nervous system, some of which are carcinogenic, causing poisoning, cancer of the liver, kidneys and stomach if eaten in small quantities and over a long period of time. This is the background for conducting research. The aim of this research is to determine whether or not the fungus Aspergillus sp. on salted fish sold at the central market of Pinrang Regency. This research uses an experimental laboratory research design, namely a proportional research design. Samples of salted fish at the central market in Pinrang Regency. Next, planting is carried out in Potato Dextrose Agare (PDA) media and then incubated again at a temperature of 37ºC for 3-7 days. Fungal colonies growing on PDA media were observed macroscopically and microscopically. The results of the examination of 7 samples found that 5 (71.43%) samples were positively identified as Aspergillus sp fungus. and 2 (28.57%) negative samples where the fungus Aspergillus sp. was not identified. Based on the research results, it can be concluded that most of the salted fish samples circulating in the central market of Pinrang Regency are still contaminated with Aspergillus sp.